Anaerobic speed reserve and performance relationships between international and world-class short-track speed skating - Deguire, S.; Sandford, G. N.; Bieuzen, F. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Short-track speed skating race distances of 500, 1000, and 1500 m that last ~40 seconds to ~2.5 minutes and require a maximal intensity at speeds beyond maximal oxygen uptake (VO2max). Recently, the anaerobic speed reserve (ASR) has been applied by scientists and coaches in middle-distance sports to deepen understanding of 1- to 5-minute event performance where different physiological profiles (speed, hybrid, and endurance) can have success.